Transitions to different patterns of interstitial lung disease in scleroderma with and without treatment. Issue 7 (12th January 2016) - Kim, Hyun J; Tashkin, Donald P; Gjertson, David W; Brown, Matthew S; Kleerup, Eric; Chong, Semin; Belperio, John A; Roth, Michael D; Abtin, Fereidoun; Elashoff, Robert; Tseng, Chi-Hong; Khanna, Dinesh; et al.
Abstract : Objectives: The aim is to investigate whether the 12-month quantitative changes in high-resolution CT (HRCT) measures of interstitial lung disease (ILD) are different, and to understand how they change, in patients with scleroderma-related ILD who receive drug therapy versus placebo. Methods: HRCT images were acquired at baseline and at 12 months in 83 participants in Scleroderma Lung Study I, a clinical trial comparing treatment with oral cyclophosphamide versus placebo. A computer-aided model was used to quantify the extent of fibrotic reticulation, ground glass and honeycomb patterns and quantitative ILD (QILD: sum of these patterns) in the whole lung and the lung zone (upper, middle or lower) of maximal disease involvement. Results: Mean QILD score decreased by 3.9% in the cyclophosphamide group while increasing by 4.2% in the placebo group in the most severe zone (p=0.01) and decreased by 3.2% in the cyclophosphamide group while increasing by 2.2% in the placebo group in the whole lung (p=0.03). Transitional probabilities demonstrated greater changes from a fibrotic to either a ground glass or normal pattern in the cyclophosphamide group and the reverse in the placebo group. Conclusions: Changes in quantitative HRCT measures of ILD provide a sensitive indication of disease progression and response to treatment. Trial registration number: NCT00004563; Post-results.